2018
DOI: 10.3126/ajms.v9i3.19294
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and hookworm co-infection and their effects on anaemia of pregnant women attending ante-natal clinic in University Teaching Hospital, Calabar, Nigeria

Abstract: Background: Malaria and hookworm infections independently have been known to cause anaemia. Coinfection of these two parasites can aggravated the morbidity of these infections with a resulting impact on anaemia especially in pregnancy. Aims and Objective: This work was aimed at assessing the prevalence of malaria and hookworm co-infection and their effects on anaemia among pregnant women in Calabar Metroplis. Materials and Methods: Giemsa stained film of venous blood was examined microscopically for malaria pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…Hookworm contributed to 0.3% of intestinal parasitic infections identified in the study. This results contrast with that of similar studies which reported higher prevalence of 3.0%, 7.0%, and 38.6%, respectively [ 6 , 7 , 22 ]. The low prevalence rate of hookworm infections observed in this study could be due to good sanitation and proper sewage disposal, as seen in the fact that many participants (78%) had their own toilet facilities rather than shared.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hookworm contributed to 0.3% of intestinal parasitic infections identified in the study. This results contrast with that of similar studies which reported higher prevalence of 3.0%, 7.0%, and 38.6%, respectively [ 6 , 7 , 22 ]. The low prevalence rate of hookworm infections observed in this study could be due to good sanitation and proper sewage disposal, as seen in the fact that many participants (78%) had their own toilet facilities rather than shared.…”
Section: Discussioncontrasting
confidence: 99%
“…The late trimesters (second and third trimesters) were associated with increased odds of intestinal parasitic infections among women. This observation is consistent with previous findings where the second and third trimesters of pregnancy presented higher odds of intestinal parasite infections than their counterparts in their first trimester [ 6 , 22 ]. In contrast to these findings, Espinosa Aranzales and her colleagues have reported that stage of pregnancy had no association with intestinal parasitic infections [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hookworm ( N. americanus ) infection is widespread in sub‐Saharan Africa with prevalence of about 29% and affecting over 200 million people. 1 , 26 , 27 Since malaria ( P. falciparum ) and hookworm ( N. americanus ) infections often coincide geographically and their coinfections elicit complex immunomodulatory effects, 11 it is imperative to evaluate how their immune response interact. We have previously established that N. americanus ‐ P. falciparum coinfection increases IgG response to GMZ2 malaria vaccine candidate in the coinfected than those with only P. falciparum infection but albendazole treatment of hookworm‐malaria coinfected individuals resulted in significant reduction in antibody responses against GMZ2 malaria vaccine candidate and constituent antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Africa with prevalence of about 29% and affecting over 200 million people. 1,26,27 Since malaria (P. falciparum) and hookworm (N.…”
Section: Hookworm (N Americanus) Infection Is Widespread In Sub-saharanmentioning
confidence: 99%
“…There is an urgent need to increase the uptake of IPTp in Nigeria. The low level of pregnant women offered IPD resonates with the little attention paid to the ght against intestinal parasites during pregnancy in Nigeria, the long clamour for its use to address this public health problem nothwithstanding [34,35]. Nigeria just like most Sub-Saharan Africa countries harbours the greatest proportion of global intestinal parasitic infections largely as a result of her socioeconomic and environmental challenges [36][37][38].…”
Section: Discussionmentioning
confidence: 99%